Social appropriation of knowledge as a key factor for local development and open innovation: A systematic review - José-María Romero-Rodríguez; María Soledad Ramírez Montoya; Inmaculada Aznar-Díaz; Francisco-Javier Hinojo-Lucena (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The social appropriation of knowledge is an emerging descriptor in political agendas, since it drives social development and innovation. The relevance of this strategy lies mainly in the fact that scientific knowledge is made available to the population for its use and application. The purposes of this study were to identify the context and purpose presented by the experiences of social appropriation of knowledge, and to analyze the linkage of the experiences with the sectors that make up the pentahelix. To this end, a systematic review methodology was proposed in the Web of Science (WOS) and SCOPUS. Following the application of the inclusion and exclusion criteria, a total of 14 articles were analyzed. The results showed the emergence of this term, the geographical location of all experiences in Latin America, and the diversity of application of knowledge to favor local development. At the same time, it is shown that the institutions belonging to the government have developed experiences of social appropriation of knowledge in all other sectors of the pentahelix. Finally, we discuss the findings and implications of this study that showed the diverse experiences of social appropriation of knowledge and investigated this concept in connection to open science.
Keywords: 650; citizen participation; open science; social appropriation of knowledge; social innovation; systematic review